Catalogue of the Anthribidae (Coleoptera: Curculionoidea) of Panama, including new country records and a key to genera - Orellana, K. Samanta; Barrios, Héctor (Zootaxa, 2021)
An updated catalogue of the Anthribidae of Panama is provided, including 134 species in 30 genera, 14 tribes and two subfamilies. A total of 44 species in the following genera are recorded for the first time in the country: Corrhecerus Schoenherr, Eugonus Schoenherr, Euparius Schoenherr, Gymnognathus Schoenherr, Nemotrichus Labram & Imhoff, Phaenithon Schoenherr, Piesocorynus Dejean, Anthiera Alonso-Zarazaga & Lyal, Ptychoderes Schoenherr, Stenocerus Schoenherr and Toxonotus Lacordaire. The genera Corrhecerus Schoenherr, Eugonus Schoenherr and Anthiera Alonso-Zarazaga & Lyal are recorded for the first time in Panama. Although more than 60 unnamed morphospecies were recognized in Panamanian and American collections, at this time no new taxa are described. An illustrated key to the genera of Anthribidae of Panama is included.